EFFECTIVENESS OF MEASURED FISHING POLICY AND POST-PRODUCTION NON-TAX STATE REVENUE MECHANISM AT KLIDANG LOR COASTAL FISHERIES PORT, CENTRAL JAVA - Nurlaela, Eli; Ripaldi, Muhamad; Saputra, Aman; Choerudin, Hery; Nababan, Sakti Pandapotan (Jurnal Penelitian Perikanan Laut (Albacore), 2025)
Capture fisheries play a crucial role in Indonesia's economy; however, their sustainability is threatened by uncontrolled fishing practices. This study analyzes the implementation of the Measured Fish Catch (PIT) policy and the post-production Non-Tax State Revenue (PNBP) payment mechanism at the Klidang Lor Coastal Fisheries Port (PPP) in Central Java. The research was conducted in early 2024 using a descriptive approach, involving 33 fishermen selected through purposive sampling. The results indicate that the migration of fishing vessel business permits to the central authority, in accordance with Government Regulation No. 11 of 2023, has been effectively implemented. Most fishermen did not encounter difficulties in reporting the Self-Assessment Report (LPM) and paying PNBP. However, issues related to the availability of weighing equipment and inaccuracies in completing the LPM still need to be addressed. The PNBP payment system based on catch volume at PPP Klidang Lor has been running efficiently and effectively, with an increase in post-production PNBP collection since March 2023. These findings contribute to the sustainable and equitable management of fisheries and can serve as recommendations for policymakers to enhance governance in the fisheries sector. Key words: capture fisheries, management, post-production Non-Tax State Revenue